Sintesis Nanopartikel Magnetik Besi Oksida (Fe3O4) Metode Green Chemistry Dengan Ekstrak Daun Sirih Merah (Piper Crocatum) - Rafiqa Khaira; Alizar Ulianas; Minda Azhar; Mawardi Anwar (Jurnal Periodic Jurusan Kimia UNP, 2020)
Magnetic nanoparticles have become an interesting topic in recent years, as magnetic nanoparticles have a greater degree of magnetism, high saturation magnetization, and ease of modification and handling. One of them is the Fe3O4 magnetic nanoparticles which are used in various fields, such as in the biomedical sector which acts as antibacterial, hyperthermia, anticancer, etc. This study aims to synthesize magnetic nanoparticles of iron oxide Fe3O4 using phenolic compounds contained in red betel leaf extract as a styling agent with a co-precipitation method based on green chemistry and to characterize them. The nanoparticles formed were measured for their magnetic force with a gaussmeter and characterized by functional groups, particle size and particle surface morphology using FTIR, XRD and SEM. The data obtained show that the optimal composition for the formation of Fe3O4 nanoparticles is to compare FeCl2: FeCl3 (0.01 mol: 0.02 mol) with a volume of 5 mL of red betel leaf extract which produces a force magnetic 0.16 mT. The characterization by FTIR shows the aromatic groups O-H, C = O carboxylate and C-H which indicate the presence of organic compounds, namely phenolic (gallic acid) which functions as a protective agent (styling agent) of Fe3O4. The XRD test obtained information on the average size of the formed nanoparticles based on the FWHM value (full width at half maximum) using Scherer's equation, which is 26.66 nm. Meanwhile, SEM data shows that the shape or morphology of the Fe3O4 magnetic nanoparticles is needle-like.Keywords — Nanoparticles, iron oxide Fe3O4, green chemistry, red betel leaf extract (Piper Crocatum)